1956
DOI: 10.1172/jci103320
|View full text |Cite
|
Sign up to set email alerts
|

The Α2 LIPOPROTEINS OF HUMAN SERUM. CORRELATION OF ULTRACENTRIFUGAL AND ELECTROPHORETIC PROPERTIES

Abstract: Two main groups of lipoproteins have been characterized in the serum of normal adults.These have been termed the a1 and the 8,/ lipoproteins on the basis of their electrophoretic mobility (1-5). The broad spectrum of low density lipoproteins that have been observed particularly in patients with arteriosclerosis by means of the analytical ultracentrifuge (6) have not been classified in terms of electrophoretic mobility because of the difficulties in characterization by classical electrophoretic procedures (7-9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1959
1959
1989
1989

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The correlations between lipoprotein bands and fractions obtained in normal subjects by different methods are shown in Figure 1. All have been substantiated experimentally (3,4,7).…”
Section: Delipidation Of Lipoproteinsmentioning
confidence: 71%
“…The correlations between lipoprotein bands and fractions obtained in normal subjects by different methods are shown in Figure 1. All have been substantiated experimentally (3,4,7).…”
Section: Delipidation Of Lipoproteinsmentioning
confidence: 71%
“…It has been suggested that the hyperlipemia of obstructive jaundice is a consequence of the retention of cholate in the plasma with a resultant trapping of plasma lipids (44)(45)(46). This explanation seems unlikely, however, because the amount of bile salt in the serum of patients with jaundice is much smaller than the amounts of leci-2 The fractions D < 1.063 and > 1.063 migrate as #-and a-globulin, respectively, on paper electrophoresis (19), while the fraction D < 1.019 migrates as a.2 globulin on zone electrophoresis (43). thin and free cholesterol (47,48) and apparently most of the bile salt is bound to albumin (49).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins were separated by electrophoresis using a Pevikon block (Mercer Consolidated Corp., Yonkers, NY) (38,39). Human LDL were used as a reference for f,-electrophoretic mobility for each Pevikon block.…”
Section: Lipoprotein Preparationmentioning
confidence: 99%